2016
DOI: 10.1002/ejic.201600855
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, Redox, and Photoinduced Electron‐Transfer Properties of the NIR‐Absorbing N‐Ferrocenyl‐2‐pyridone BODIPYs

Abstract: Mono-and di-(N-ferrocenyl-2-pyridone)-containing BODIPYs were prepared using a set of ferrocene-enamine cyclization reactions. The target compounds were characterized by UV-Vis, NMR, and mass spectrometry, while their redox properties were probed by the electrochemical, spectroelectrochemical, and chemical oxidation methods. Redox properties of the di-(ferrocenyl)-containing BODIPY are suggestive of a lack of electronic coupling between the two ferrocene groups. Oxid-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 101 publications
4
21
0
Order By: Relevance
“…Oxidation of the ferrocene substituent(s) in BODIPYs and their analogues under chemical or spectroelectrochemical oxidation conditions reduces the effectiveness of such electron-transfer pathway and results in partial restoration of the fluorescence, which can be again suppressed by the reduction of ferricinium group to ferrocene (Figure 10). [7,10,11,16,17,25,29,33] Similar partial restoration of the steady-state fluorescence was also reported for ferrocene-containing BODIPY system in viscous solvents [32] and upon addition of water [28] to a solution of some ferrocene-containing BODIPYs. It was speculated that the dihedral angle (and thus degree of conjugation between ferrocene group and chromophore's π-system) is responsible for the fluorescence increase in the former case, while partial degradation of the organometallic fragment is responsible for fluorescence increase in the latter.…”
Section: Fluorescence and Photo-induced Electron-transfer Propertiesmentioning
confidence: 65%
See 4 more Smart Citations
“…Oxidation of the ferrocene substituent(s) in BODIPYs and their analogues under chemical or spectroelectrochemical oxidation conditions reduces the effectiveness of such electron-transfer pathway and results in partial restoration of the fluorescence, which can be again suppressed by the reduction of ferricinium group to ferrocene (Figure 10). [7,10,11,16,17,25,29,33] Similar partial restoration of the steady-state fluorescence was also reported for ferrocene-containing BODIPY system in viscous solvents [32] and upon addition of water [28] to a solution of some ferrocene-containing BODIPYs. It was speculated that the dihedral angle (and thus degree of conjugation between ferrocene group and chromophore's π-system) is responsible for the fluorescence increase in the former case, while partial degradation of the organometallic fragment is responsible for fluorescence increase in the latter.…”
Section: Fluorescence and Photo-induced Electron-transfer Propertiesmentioning
confidence: 65%
“…In the most of case, DFT and TDDFT calculations using standard hybrid (20 % of Hartree-Fock exchange) B3LYP exchange-correlation functional coupled with doubleor triple-ζ quality basis sets provide a good agreement between theoretical and experimental data. [6][7][8][9]11,13,16,19,21,[23][24][25]29,32,35] In several cases of the ferrocenyl-containing azaBODIPYs and BOPHY, however, it was shown that use of the hybrid TPSSh (10 % of Hartree-Fock exchange) results in better correlation between theoretical and experimental data. Modified from reference [6] .…”
Section: N Nemykin Et Almentioning
confidence: 99%
See 3 more Smart Citations